(untitled) (Archives of Mechanics - Test, 2001)
The thermodynamics of a crystal lattice reorientation process proceeding on low angle grain boundary is presented. In material science, the influence of lattice misorientation on the grain boundary energy is well established. On the other hand, in thermodynamics of discontinuity surface the influence of misorientation vector on the surface energy is usually ignored as yet. Therefore, in the present paper, attention is focused on this influence. To obtain the driving forces conjugate to relative grain reorientation, the continuum theory of dislocations has been applied. Starting from the energy balance law and assuming that the free energy of discontinuity surface depends strongly on the jump in crystal orientation field, the mathematical relations for the misorientation vector and the conjugated thermodynamic force are derived. The mentioned force contributes to the total driving force governing the grain boundary migration process. The problem of constitutive modelling of the surface motion is considered. The main result of this analysis is the incorporation of grain orientation jump into the thermodynamic description of driving forces of the grain reorientation process.